Spring flooding and recurring evacuations of Kashechewan First Nation, northern Ontario, Canada. (September 2021) - Khalafzai, Muhammad-Arshad K.; McGee, Tara K.; Parlee, Brenda
Abstract: Floods and evacuations due to flooding can increase vulnerability and affect community resilience. This article examines how the Kashechewan First Nation, located in the flood-prone Subarctic southwestern James Bay region of Canada, is affected by the frequent risk of spring flooding. Kashechewan, an isolated and remote Indigenous community, is located along the Albany River in northern Ontario. Kashechewan First Nation has been evacuated 14 times to at least 22 host communities across Ontario since 2004 (consecutively from 2004 to 2008 and 2012–2019) because of actual flooding events or flooding risk and the potential failure of the dike that surrounds the community. Through a collaboration with the First Nation, qualitative semi-structured interviews were completed with 41 participants. Results show that spring flood risk has significantly increased the community's physical and socio-cognitive vulnerability. Flooding frequently impacts community infrastructure, traditional spring hunting and harvesting, and the local economy. It also significantly increases the stress and anxiety of residents every year as spring approaches. Dealing with the regular flooding risk and recurring emergency experiences have improved the community's disaster preparedness and coping capacity, but residents' evacuation experiences negatively affect their well-being during and after the evacuations. The short-term responses to the physical vulnerability of people frequently experiencing the elevated hazards risks help increasing specific resilience-building and coping capacity in the short-run. However, such short-term responses can also produce greater vulnerability in the long-term. Similarly, if the long-term adaptation responses for resilience-building do not consider the short-term coping capacities and community-specific ground realities, they can significantly increase the physical vulnerability of residents.